Правовые взаимоотношения автора и издательства - Аврамова, О. Е.; Зайцева, А. А. (НТУ "ХПИ", 2013)
The article deals with the problems of establishing legal relations of the author and publisher. Establishing the legal status of these subjects. The article defines the types of contracts that are concluded between the author and publisher, in particular, is characterized by the author's agreement.
Keywords: статус правовой; договор авторский; произведение; литература; наука; искусство; правоотношения